Validation of the Aquanex system to assess in-water forces during aquatic exercise - Catarina Santos; Mário Costa; Daniel Almeida; Nuno Garrido; Tiago Barbosa; Sérgio Rosa (Motricidade)
The aim of this study was to perform a validation of the Aquanex system to assess in-water forces during aquatic exercise. One sensor (Type A) that composes the differential pressure system (Aquanex v.4.1, STR, USA) was placed inside a wind tunnel (Axial Propellor Fan, England), this last being considered as the gold standard technique for measurement. A frequency inverter was used to control a range of twenty-two frequencies. The mean force (FMEAN, N) acting on the sensor and in the wind tunnel model was measured. The validation criteria were defined as follows: (i) p>0.05 in a paired t-test; (ii) R2≥0.49 in a simple linear regression model; and (iii) at least 80 % of the plots within the limits of agreement in the Bland-Altman plots. The results showed no differences between both methods (p=0.884). A significant relationship with a high effect (R2=0.573, p<0.001) was found, as well as a small bias (0.002 N) between the two methods. Thus, the Aquanex system seems to be valid for assessing the in-water forces as it meets all the validation criteria.